Implikasi Pengurangan Pemakaian Plastik Sekali Pakai Terhadap Volume Sampah di TPA Suwung - I Gusti Made Yudha Pramana; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Preferensi Hukum, 2024)
The waste problem in Indonesia is getting worse, including the problem of landfills in Bali getting full every day. The waste problem is not only a matter for the government, but also for the community. The use of single-use plastics is an important thing that must be considered to find the best solution. This research aims to find out the legal policies that can help overcome the waste problem in Indonesia in general and Bali in particular. Based on this, this research will discuss how the impact of reducing the use of single-use plastics on the environment, society and its relation to storage in Suwung landfill and how the government's efforts as a policy maker in overcoming the problem of single-use plastic waste in Suwung landfill. The research method used is an empirical legal research method that uses a fact-based approach and analyzes legal concepts through social problems. The results obtained from this research are that the reduction in the use of single-use plastics provides a solution to the waste problem at Suwung Landfill so that less waste enters and if the reduction in the use of single-use plastics is applied more widely, plastic waste generation can be minimized, and regulations made by the government emphasize solutions from various aspects of the waste problem. However, many people still violate the regulations in the field.